PROFIL LAPISAN PEMAHAMAN KONSEP TURUNAN FUNGSI DAN FOLDING BACK MAHASISWA CALON GURU MATEMATIKA BERDASARKAN GENDER (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2016)
This research aimed to describe the profile of understanding layers of understanding the concept of the function’s derivative and folding back college student prospective teachers of mathematics by gender. This study used a qualitative descriptive approach . The data obtained is validated, then the analysis step-by- step reduction, data presentation, categorization, interpretation and inference. The analysis process is guided to the understanding of the model which hypothesizes Pirie&Kieren owned eight layers understanding students. The results showed that there was no difference between the achievement of a layers of understanding of the subject of women and man, both of them have an indicator layers of understanding ie; primitive knowing, image making, image having, property noticing, formalising, observing and structuring, then reaching also the first indicator (In1) of inventising layer, and indicators "ask questions about graphs the third-degree polynomial function" that leads to the second indicator (In2) of inventising layer. Based on the indicators of these, both subjects can be put in a category understanding layer ie oida inventising. But both subjects distinc 10 (ten) items the process of achieving this understanding, including in providing an example of a polynomial of fourth degree, woman began with equations, determining the intersections with the X-axis or the line x=k, drawing the X-axis and Y-axis, plot the points of intersection, divide into several intervals, then calculate some value functions to perform each test point intervals, and then describe the graph. Meanwhile, the man gave an example of a polynomial of fourth degree in the form of images, then determine the similarities, each interval point test done to test and verify that the correct graph drawn afterwards. Women made twice folding back the form of "off-topic", and man made that once. Instead of man performed twice folding back the form "working on the deeper layers", both subjects do not perform folding back the form "cause discontinuous".Key words : understanding layers, folding back, gender